Forming Ethnic Identity in Primary School Children Through Ethno-Cultural Heritage - R R Nakohova; Z S Kipkeyeva (Peoples' Friendship University of Russia (RUDN University), 2012)
The article analyzes the ways of forming ethnic identity at the primary school age through the ethno-cultural heritage of nations. The structural components of the ethnic identity and the study of feasibility of the personality developing potential of the experimental program are considered.